Ground beetles (Coleoptera: Carabidae) inhabiting anthropogenic habitats in the lower delta of the Paraná river, Argentina: geographic distribution and ecological characteristics - Nanni, Analía Soledad (2017)
The primary aims of this paper were to provide the first inventory of carabid beetles collected in five different anthropogenic habitat types of the Lower Delta of the Paraná River, to describe their main ecological characteristics and to provide information on their distribution range in ecoregions, subregions and ecosystem complexes of Argentina and across the Neotropical region. Species were grouped according to six classes of distributions in relation to their presence in the Delta of the Paraná River. In addition, rarefaction curves were built in order to compare the seasonal species richness. We collected 1486 individuals belonging to 48 species. The southernmost distribution limit of 50% of the species is located south of the Delta region. Moreover, 21% of the species are confined to the Delta and Islands of the Parana and Uruguay Rivers ecoregion and to localities within the neighbouring ecoregions of Espinal and Pampa. Most (63%) of the species were zoophagous and 25%were either omnivorous or seed eaters; 52%were hydrophilous, 44%mesophilous and one was xerophilous. The high number of species found in this ecoregion emphasising its importance as a biodiversity hotspot of South American carabids. Human activities have led to changes in the landscape of the Delta Islands which could favour the establishment of mesophilous and xerophilous species from other ecoregions. Seasonal carabid richness is higher in the warm seasons (spring and summer) compared with the cold seasons (autumn and winter). Although, the highest absolute richness was found in the most anthropised habitat types, secondary forests had exclusive species, showing the importance of preserving the ecological mosaic of the landscape.